PRINCIPLES OF TRANSITION OF PUBLIC SERVICE TO OMNICHANNEL DIGITAL STRATEGY - E. V. Vasilieva (Вестник университета)
The principles of formation of a digital organization and the main steps of transformation of customer experience in the field of public services on the basis of omnichannel have been defined. The basis for the implementation of digital principles should be changes in personnel management, including a focus on engagement, motivation, result orientation, team building understanding of the client. The results of assessing the demand for technological trends that can be used to expand the composition of digital services of the public service have been presented in the article. The task of rapid implementation of digital interaction of public services in the simplification of the procedure of registration of documents has been highlighted separately. The key areas for improving the processes of interaction between citizens and the civil service, which can be created in digital form primarily, have been determined. The main principle of the selection of priority areas of application of technologies was the readiness of citizens to innovative changes (digital maturity), as well as the sufficiency of resource support for transformative processes.